RAFT synthesis and stimulus-induced self-assembly in water of copolymers based on the biocompatible monomer 2-(Methacryloyloxy)ethyl phosphorylcholine - Yu, B.; Lowe, Andrew; Ishihara, K. (American Chemical Society, 2009)
absReversible addition-fragmentation chain transfer (RAFT) radical polymerization, mediated by 4-cyanopentanoic acid dithiobenzoate and 4,4'-azobis(4-cyanovaleric acid) (V-501) in water at 70°C, of biocompatible 2-(meth- acryloyloxy)ethyl phosphorylcholine (MPC) yields a macro-chain transfer agent (CTA) that was employed in the synthesis of a range of stimulus-responsive AB diblock copolymers in protic media. Well-defined block copolymers of varying molar composition, with narrow molecular weight distributions (M w/M n = 1.10-1.24) were prepared with N,.N-diethylacrylamide (DEAm), 4-vinylbenzoic acid (VBZ), N(3-sulfopropyl)-N- methacryloyloxyethyl- N,N-dimethylammonium betaine (DMAPS), and the newly synthesized N,N-di-n-propylbenzylvinylamine (Dn- PBVA) in either methanol, 2,2,2-trifluoroethanol, or aqueous media. When a combination of 1H NMR spectroscopy and dynamic light scattering is used, it is shown that all block copolymers are capable of existing as molecularly dissolved chains in aqueous media with average hydrodynamic diameters of ~6-7 nm provided the aqueous environment is appropriately tuned. Similarly, these unimers can be induced to undergo self-assembly in the same aqueous environment provided the correct external stimulus (change in temperature, pH, or electrolyte concentration) is applied. In such instances, aggregates with average sizes in the range of ~22-180 nm are formed and are most likely due to the formation of polymeric micelles and vesicles. Such self-assembly is also completely reversible. Removal, or reversal, of the applied stimulus results in the reorganization to the unimeric state. ©2009 American Chemical Society.